2005
DOI: 10.1029/2004gb002401
|View full text |Cite
|
Sign up to set email alerts
|

A 3‐year field measurement of methane and nitrous oxide emissions from rice paddies in China: Effects of water regime, crop residue, and fertilizer application

Abstract: [1] A 3-year field experiment was conducted to simultaneously measure methane (CH 4 ) and nitrous oxide (N 2 O) emissions from rice paddies under various agricultural managements including water regime, crop residue incorporation, and synthetic fertilizer application. In contrast with continuous flooding, midseason drainage incurred a drop in CH 4 fluxes while triggering substantial N 2 O emission. Moreover, N 2 O emissions after midseason drainage depended strongly on whether or not fields were waterlogged d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

60
459
13
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 657 publications
(534 citation statements)
references
References 63 publications
(84 reference statements)
60
459
13
2
Order By: Relevance
“…Meanwhile, soil water content was usually considered to be another important regulator of CH 4 fluxes or uptakes (Zou et al 2005;Wang et al 2015). Sustainable water logging would favor the existence of methanogens and led to more CH 4 fluxes (Zou et al 2005), which is also supported by our results (Figs. 1b and 3b).…”
Section: Dependence Of Soil Ch 4 and N 2 O On Soil Propertiessupporting
confidence: 87%
See 3 more Smart Citations
“…Meanwhile, soil water content was usually considered to be another important regulator of CH 4 fluxes or uptakes (Zou et al 2005;Wang et al 2015). Sustainable water logging would favor the existence of methanogens and led to more CH 4 fluxes (Zou et al 2005), which is also supported by our results (Figs. 1b and 3b).…”
Section: Dependence Of Soil Ch 4 and N 2 O On Soil Propertiessupporting
confidence: 87%
“…While in orchard fields, soil DOC contents decreased due to the improved soil aeration and increased mineralization activity (Weller et al 2016). Thus, our result confirmed that higher CH 4 fluxes were observed from paddy soils where DOC contents were higher (Zou et al 2005;Yao et al 2012). Studies also showed that the higher level of DOC contents may have enhanced C availability thus controlled N 2 O emissions through its influence on nitrify and denitrifying activity (Burger et al 2005).…”
Section: Effects Of Land Use Conversion On Soil Ch 4 and N 2 O Fluxessupporting
confidence: 81%
See 2 more Smart Citations
“…However, incorporation of straw also increases CH 4 production and emissions (Denier Van Der Gon and Neue 1995;Zou et al 2005). Several incubation studies have shown a highly dynamic structure of methanogenic archaeal communities during straw decomposition, with members responding differently to organic residue type, incubation temperature, and duration of incubation (Conrad and Klose 2006;Peng et al 2008;Conrad et al 2012;Lu et al 2015).…”
Section: Introductionmentioning
confidence: 99%